2007
DOI: 10.1089/end.2006.0163
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Prostate Size in Robot-Assisted Radical Prostatectomy

Abstract: Although a large prostate volume is associated with a slight increase in short-term urinary complications postoperatively, it should not be considered a contraindication for the experienced surgeon. This higher risk raises the question of a possible need for longer catheterization in this subset of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
56
2
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 12 publications
4
56
2
9
Order By: Relevance
“…27 It has been suggested that wider dissection of the bladder neck for large prostates can contribute to this association. 28 While smaller prostate volume was associated with continence at 1 month on univariate analysis, this characteristic was not an independent predictor of continence on multivariate analysis.…”
Section: Discussionmentioning
confidence: 81%
“…27 It has been suggested that wider dissection of the bladder neck for large prostates can contribute to this association. 28 While smaller prostate volume was associated with continence at 1 month on univariate analysis, this characteristic was not an independent predictor of continence on multivariate analysis.…”
Section: Discussionmentioning
confidence: 81%
“…Boczko et al [23] examined the effects of prostate size on treatment outcomes after extraperitoneal RARP. They evaluated 355 patients who underwent RARP and compared patients with prostate weight <75 g (n = 319) with those having glands ≥75 g (n = 36).…”
Section: Discussionmentioning
confidence: 99%
“…are expected to overcome the technical challenges and inferior surgical outcomes associated with larger prostates. However, the impact of prostate size on surgical and oncological outcomes in RARP has been controversial [1,[4][5][6][7][8][9]. Most research addressing this issue was based on the pathological prostate weight (g) [4][5][6][7][8].…”
mentioning
confidence: 99%